Two different and robustly modeled DNA binding modes of Competence Protein ComP - systematic modeling with AlphaFold 3, RoseTTAFold2NA, Chai-1 and re-docking in HADDOCK - Stian Aleksander Helsem; Kristian Alfsnes; Stephan A. Frye; Alexander Hesselberg Løvestad; Ole Herman Ambur (PLoS ONE, 2025)
The competence protein ComP is a Type IV minor pilin and the extracellular DNA binding protein involved in natural transformation in the human pathogens Neisseria gonorrhoeae , Neisseria meningitidis, Eikenella corrodens and related Neisseriaceae bacteria. Details of the DNA binding mode of ComP is enigmatic, and the 3D structure of the DNA:: protein complex remains unresolved. Here we characterize the ComP orthologs in a set of Neisseriaceae family members, model their common structural domains and their interaction with different preferred 12 base pair long DNA binding motifs, DNA Uptake Sequences (DUS) and scrambled versions of these. Through systematic in silico modeling using AlphaFold 3, RoseTTAFold2NA, and Chai-1 and model comparisons, we bring a new understanding of the interactions between DNA and ComP. We report six distinct binding modes of which two, here named Epsilon and Gamma, were robustly modeled across platforms and different ComPs. The characteristics and robustness of the predicted models and DNA binding modes from each tool are assessed and discussed. This work expands the knowledge on the ComP:: DUS interaction and guides further wet- and dry-lab systematic and experimental characterization of these complexes through which molecular and clinical interventions may be developed.